(untitled) (Journal of Medicine, 2020)
From late December’19 till the end of August 2020, in this nine months period, world has lost more than eight hundred thousands people due to COVID-19 pandemic. Clinical data on COVID-19 in Bangladesh is less. The objective of our study was to evaluate demographic and clinical profile with in a defined period among COVID-19 Bangladeshi Patients in a Tertiary Care Private Medical College Hospital of Dhaka. We conducted a retrospective descriptive study on epidemiological & clinical profile along with short term treatment outcomes of 190 COVID-19 patients from COVID dedicated unit of Popular Medical College Hospital (PMCH) during the period of 18th June to 22nd August 2020 (2 months) with a pre-determined case record form (CRF).Among this 190 patients, mean age was found to be 53 years. Highest percentage of patients (44%) belonged to 41-60 years of age. Regarding gender distribution, two-third patients were male (65%) & one-third patients were female (35%). The predominant symptoms of our enrolled patients were fever (88%),cough (81%) , dyspnoea (58%) & fatigue( 50%). Around half of the patients had been suffering from Hypertension (54%) and Diabetes (47%). Almost half of our patients belonged to moderate severity (48%).The duration of Hospital stay was from 1-36 days, mean was 7 days. There was significant difference for severe and non-severe cases (p value 0.01). J MEDICINE JUL 2020; 21 (2) : 82-88